Peripheral Injection of SB203580 Inhibits the Inflammatory-Dependent Synthesis of Proinflammatory Cytokines in the Hypothalamus. (4th June 2014) - Herman, Andrzej P.; Krawczyńska, Agata; Bochenek, Joanna; Antushevich, Hanna; Herman, Anna; Tomaszewska-Zaremba, Dorota
Abstract : The study was designed to determine the effects of peripheral injection of SB203580 on the synthesis of interleukin- (IL-) 1 β, IL-6, and tumor necrosis factor (TNF) α in the hypothalamus of ewes during prolonged inflammation. Inflammation was induced by the administration of lipopolysaccharide (LPS) (400 ng/kg) over 7 days. SB203580 is a selective ATP-competitive inhibitor of the p38 mitogen-activated protein kinase (MAPK), which is involved in the regulation of proinflammatory cytokines IL-1 β, IL-6 and TNF α synthesis. Intravenous injection of SB203580 successfully inhibited (P < 0.01 ) synthesis of IL-1 β and reduced (P < 0.01 ) the production of IL-6 in the hypothalamus. The p38 MAPK inhibitor decreased (P < 0.01 ) gene expression of TNF α but its effect was not observed at the level of TNF α protein synthesis. SB203580 also reduced (P < 0.01 ) LPS-stimulated IL-1 receptor type 1 gene expression. The conclusion that inhibition of p38 MAPK blocks LPS-induced proinflammatory cytokine synthesis seems to initiate new perspectives in the treatment of chronic inflammatory diseases also within the central nervous system. However, potential proinflammatory effects of SB203580 treatment suggest that all therapies using p38 MAPK inhibitors should be introduced very carefully with analysis of all expected and unexpected consequences of treatment.